Innovation or episodes? Multi-scalar analysis of governance change in urban regeneration policy in South Korea. (September 2019) - Seo, Bo Kyong; Joo, Yu-Min
Abstract: Governance-beyond-the-state has been widely adopted in urban politics in recent decades of global neoliberalism. However, how the governance change actually takes place in the planning system needs careful substantiation and contextualisation. By applying the 'levels of governance' concept, this paper examines diverse factors of governance innovation with a reference to the recent participatory urban regeneration policy in South Korea. Through multi-scalar analysis of the comparative case studies of three districts in the city of Daegu, we explain a combination of various factors at the local level that has a significant influence on governance innovation. We also highlight that governance innovation is engendered on the basis of the material and relational resources available at other spatial scales and involves multi-scalar institutional restructuring. This multi-scalar dimension would broaden our understanding of what makes governance change possible and how it takes place. Highlights: Governance change is an inter-scalar and multi-directional process. Innovative episodes need institutionalisation into governing processes to be sustainable. Place identity and the role of key actors affect governance change. The cultural assumption on the urgency of regeneration also facilitates innovation.